Sources on the political history and leadership of the states of Central Asia in the 18th–19th centuries - Ibrohimzoda Gulruh Shokirjon qizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides information about the historical studies and sources concerning the history of the Bukhara Emirate, Khiva and Kokand Khanates in the 18th-19th centuries.